2015
DOI: 10.1177/0278364915584806
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid motion/force control of multi-backbone continuum robots

Abstract: The recent growth of surgical applications exploiting continuum robots demands for new control paradigms that ensure safety by controlling interaction forces of tele-operated end-effectors. In this paper, we present the modeling, sensing and control of multi-backbone continuum robots in a unified framework for hybrid motion/force control. Multi-backbone continuum robots allow to estimate forces and torques at the operational point by monitoring loads along their actuation lines without the need for a dedicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(93 citation statements)
references
References 55 publications
0
93
0
Order By: Relevance
“…For example, commercial cardiac ablation catheters often have only a distal position and orientation sensor for visual feedback [51,52]. Bajo et al [45,[53][54][55] and Jeon and Yi [56] utilized an understanding of the mechanics of their manipulator to infer contact forces on the manipulator using a number of interspersed magnetic position sensors and a stiffness model of the continuum backbone. Groom et al showed these methods on cadavers for a vocal fold surgery application [57].…”
Section: State-of-artmentioning
confidence: 99%
“…For example, commercial cardiac ablation catheters often have only a distal position and orientation sensor for visual feedback [51,52]. Bajo et al [45,[53][54][55] and Jeon and Yi [56] utilized an understanding of the mechanics of their manipulator to infer contact forces on the manipulator using a number of interspersed magnetic position sensors and a stiffness model of the continuum backbone. Groom et al showed these methods on cadavers for a vocal fold surgery application [57].…”
Section: State-of-artmentioning
confidence: 99%
“…inter-module and skin force/torque sensors to discern interaction forces with the trocar port or en-route organs, and a more general hybrid force-motion controller, expanding the frameworks proposed in [43], [44] to multisegment soft manipulators with variable stiffness. Although such improvements would emphasize the potential superiority of soft continuum manipulators in safely following tortuous paths when navigating inside the human body, the focus of this paper and its experiments is to demonstrate the capability of the proposed system to follow 2D trajectories with its end-effector while controlling contact force matching the accuracy levels that teleoperated rigid-link surgical robots are capable of [45].…”
Section: Ex-vivo Tissue Cutting Using Electric Diathermymentioning
confidence: 99%
“…Although the application of position control is well suited for the tasks in which the robot is not constrained by any object in the workspace; a successful and safe interaction between a robot and its environment is required in many automated manufacturing systems, sometimes within a non-explicitly known environment. According to [1], interaction force and motion control in robotics are generally divided in two main approaches; impedance control and hybrid motion/force control. While impedance control [2] stands for adjusting the mechanical impedance of the contact point with a rigid environment, the main concept of hybrid position/force control [3] is based on subjecting the end effector of the manipulator to external constraints which are experienced in the form of interaction forces when the manipulator interacts with the environment.…”
Section: Introductionmentioning
confidence: 99%